Effects of Facebook-based e-portfolio on ESL learners' writing performance. Issue 1 (2nd January 2021) - Barrot, Jessie S.
ABSTRACT: One recent development in writing pedagogy is the use of Web 2.0 technologies such as Facebook. Although there have been a lot of studies on Facebook use in writing classrooms, very few studies have explored it as an e-portfolio platform. Thus, this quasi-experimental study attempted to investigate the effects of Facebook-based e-portfolio on L2 learners' writing performance. The study involved 89 L2 English students from four English classes. Two classes were assigned to the treatment group ( N = 48) which used a Facebook-based e-portfolio, while the other two were assigned to the control group ( N = 41) which was exposed to a conventional portfolio. Using both quantitative and qualitative data, findings demonstrated that students who used the Facebook-based e-portfolio have outperformed those from the conventional portfolio group. These results were attributed to Facebook's interactive features, flexibility, accessibility as well as its ability to expose students to social pressure and increase their audience awareness. Implications for L2 writing, assessment, and future studies are discussed.